Studying Crime Trends: Introduction to the Special Issue - Rosenfeld, Richard (Journal of contemporary criminal justice, 2024)
The study of change over time in crime rates is as old as criminology itself. A fundamental question about crime rates is whether they are moving up or down. This special issue of the Journal of Contemporary Criminal Justice brings together recent research on trends in crime and related issues, such as arrests, imprisonment, terrorism, and reporting crimes to the police. These papers show that the study of crime trends is alive and well in criminology and point to innovative data sources, methods, and topics that deepen our understanding of how and why crime rates move up and down over time.